2019
DOI: 10.1038/s41467-019-13063-y
|View full text |Cite
|
Sign up to set email alerts
|

From small-scale forest structure to Amazon-wide carbon estimates

Abstract: Tropical forests play an important role in the global carbon cycle. High-resolution remote sensing techniques, e.g., spaceborne lidar, can measure complex tropical forest structures, but it remains a challenge how to interpret such information for the assessment of forest biomass and productivity. Here, we develop an approach to estimate basal area, aboveground biomass and productivity within Amazonia by matching 770,000 GLAS lidar (ICESat) profiles with forest simulations considering spatial heterogeneous env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…For example, one can analyse the influence of microclimate in a forest on carbon dynamics or the influence of speciesspecific water use strategies and how this might affect the water cycle due to changes in interception, precipitation or soil water content [27,67] Individual-based models based on forest inventories including tree size as well as species composition with a species-specific parametrisation enables a transfer to other sites. This approach could also facilitate largescale analysis of carbon flux dynamics on tree level by linking model simulations with remote sensing (e.g., Rödig et al [68]).…”
Section: The Benefit Of Modelling Forest Carbon Fluxesmentioning
confidence: 99%
“…For example, one can analyse the influence of microclimate in a forest on carbon dynamics or the influence of speciesspecific water use strategies and how this might affect the water cycle due to changes in interception, precipitation or soil water content [27,67] Individual-based models based on forest inventories including tree size as well as species composition with a species-specific parametrisation enables a transfer to other sites. This approach could also facilitate largescale analysis of carbon flux dynamics on tree level by linking model simulations with remote sensing (e.g., Rödig et al [68]).…”
Section: The Benefit Of Modelling Forest Carbon Fluxesmentioning
confidence: 99%
“…Recent studies (based on individual-based forest growth models) [31,66,67] demonstrated how remote sensing information can be combined with forest models to provide additional information about forests. Forest models simulate the long-term dynamics of forests (based on single trees) and can estimate forest successional states by matching simulated and remotely sensed vertical leaf profiles [66]. Our approach-which is based on related methodological assumptions-thus, also appears promising for estimating the successional state (caused, e.g., by disturbances).…”
Section: Future Applications and Challengesmentioning
confidence: 99%
“…The importance of the Amazonian basin as one of the largest ecosystems on Earth is extensive, from being the richest region hosting 25% of global biodiversity to being a huge carbon sink that eliminates up to 20% of excess atmospheric carbon and contributes to the biogeochemical functioning of the Earth system 1 3 . The Amazon is exposed to different altering factors such as wind blow-downs 4 , droughts 5 , but also deforestation and intensive fires 6 .…”
Section: Introductionmentioning
confidence: 99%